Portal Venous Blood Circulation Supports Immunosuppressive Environment and Pancreatic Cancer Circulating Tumor Cell Activation. Issue 1 (January 2017) - Arnoletti, Juan Pablo; Zhu, Xiang; Almodovar, Alvin J.O.; Veldhuis, Paula P.; Sause, Ryan; Griffith, Elizabeth; Corpus, George; Chang, Jeffrey C.C.; Fanaian, Na'im; Litherland, Sally A.
Abstract : Objectives: Aggressive spread and liver metastases are predominant features of pancreatic ductal adenocarcinoma (PDAC). This study investigates activation of PDAC circulating tumor cells (CTC) and immunosuppression in the portal venous system. Methods: Portal venous and peripheral blood were collected during pancreaticoduodenectomy from patients with PDAC (n = 21) or other non-PDAC pancreatic conditions (n = 20). Circulating tumor cells were isolated by fluorescence-activated cell sorting and characterized for messenger RNA (mRNA) expression and acetylated chromatin encoding K-RAS exon 12 mutation ( K-RASmut ). Myeloid-derived suppressor cells (MDSC) were identified using flow cytometry. Results: Pancreatic ductal adenocarcinoma K-RASmut mRNA expression in portal venous blood CTC was significantly elevated compared with preoperative and postoperative peripheral blood ( P = 0.0123 and P = 0.0246, respectively). There was no significant variation in total CTC numbers between portal and peripheral blood. Portal venous M-MDSC were elevated compared with peripheral blood in PDAC patients ( P = 0.0065). M-MDSC increases correlated with K-RASmut mRNA-expressing CTC present in PDAC portal blood ( P < 0.0001). Conclusions: Association of MDSC with active CTC in portal venous blood may support immunosuppression within the portal venous circulation to promote PDAC CTC survival.